(untitled) (American Journal of Islam and Society, 2025)
This issue of the American Journal of Islam and Society comprises three primary research articles, which respectively engage the themes of political obedience, the relationship between religiosity and sustainable behavior, and the interpretation of texts. First, we have Bachar Bakour’s article, “Reconceptualizing Political Obedience in Islamic Thought: An Analytical study of Ḥadīth Literature.” Bakour examines the highly important question – both historically and today – of obedience to the ruler in the Islamic tradition. Next, we have the intriguing and exhaustively researched work by Sahibzada Muhammad Hamza and Nasim Shah Shirazi, “The Role of Religiosity in Shaping Sustainable Behavior: A Global Perspective.” Their article provides an important contribution to the current literature on sustainable behavior and religiosity by moving beyond small studies of local contexts to provide a global analysis over several decades. Our third research article for this issue is Naveed Anjum’s study, “Textual Authority and Modern Urdū Exegetical Interpretations: A Case Study of Q.4:34.” Here, Anjum provides a thoroughgoing exploration of key South Asian exegetes writing in Urdū in the modern period, ranging from the 20th century to today. Lastly, this issue also includes an insightful forum piece by Ismail Hashim Abubakar on scholarly debates in Nigeria around the phenomenon of the Boko Haram insurgency. Taken together, these contributions offer a wide range of thought-provoking and insightful points of departures for further exploration in a diversity of fields.